Integrating, reconciling, breaking:: the Lisbon Courts between Portuguese from both hemispheres (1821-1822) (Ágora Journal, 2021)
On August 24, 1820, the “Porto Revolution” broke out in Portugal, a movement that gave rise to the Lisbon Courts. The purpose of this article is to analyze the main aspects of the dynamics that were present in the discursive pleading of this assembly, understood here as the founding institution of modern Portuguese-Brazilian constitutionalism. The discussion will start from an analysis of the languages ​​that formed the “vintista” political set of ideas, focusing on the debates about the origin and the exercise of sovereign power that would relate to the intentions of transforming Portugal into what Fernando Catroga calls an Estado-nação Império. It is concluded that the disputes and disagreements fomented by the Lisbon Courts in this sense have generated projects for the formation of Brazil as an independent nation.
Keywords: Sovereignty; Lisbon Courts; Constitucionalism